Chronic Hand Eczema Guidelines From an Expert Panel of the International Eczema Council. Issue 5 (September 2021) - Silverberg, Jonathan I.; Guttman-Yassky, Emma; Agner, Tove; Bissonnette, Robert; Cohen, David E.; Simpson, Eric; Wollenberg, Andreas; Thyssen, Jacob P.
Abstract : Background: Assessment of chronic hand eczema (CHE) is complex and warrants standardization. Objective: We sought to guide clinicians on the assessment of CHE. Methods: An electronic questionnaire regarding the diagnosis and assessment of CHE was completed by councilors (n=45) of the International Eczema Council, an international group of clinicians and researchers with expertise in CHE. The survey consisted of 52 statements for consensus. Results: Overall, nine statements (17.3%) had strong, twenty-three (44.2%) moderate, 12 (23.1%) low, and 8 (15.4%) very low levels of agreement. Five statements had considerable disagreement, including the value of conducting a skin biopsy (62.2% disagreement), investigating for possible type 1 reactions (60.0%), conducting a fungal culture (44.4%), finding no history of relevant allergens and/or irritants (31.1%) in most or all cases, and performing patch testing irrespective of lesion location and morphology (28.9%). Agreement was generally highest among respondents from Europe (28.6–77.8% agreement), followed by Asia (7.1%–35.7% agreement), North America (0%–35.5% agreement), and other (0%–13.3% agreement). Conclusions: There were substantial differences of agreement, suggesting there are many knowledge and/or practice gaps with respect to CHE. Future research is needed to inform evidence-based and/or consensus guidelines for CHE.